PROBLEMS OF CHILDHOOD AND EDUCATION IN CHICKEN'S WORKS. - Xamrayev Sevinch Zarifboyevna; Kenjayeva Muxlisa Bahadirovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
This article delves into the thematic exploration of childhood and education in the works of Chicken, a prominent contemporary author known for his insightful portrayal of societal issues. Through a comprehensive analysis of Chicken's literary oeuvre, this study elucidates the multifaceted challenges children and the educational system face. Chicken's narratives often depict the struggles of young protagonists navigating complex social, familial, and educational environments, thereby shedding light on pertinent issues such as poverty, abuse, neglect, and inadequate schooling. Furthermore, the article examines how Chicken skillfully addresses these problems with sensitivity and nuance, offering profound insights into the impact of childhood experiences on individual development and societal structures. By exploring the intersection of childhood and education in Chicken's works, this study contributes to a deeper understanding of contemporary literary representations of these central themes and their relevance to broader social discourse.